Triple whammy blues; trial by publicity; mad about sting [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Summary: Deals with the one-peso-levy on oil and gasoline in 1994; the controversial issue of the Elsa Castillo film show; and the exclusive interview with rock singer and musician, Sting.